Analisis Keterlaksanaan Standart Operational Procedure (SOP) Persiapan Bahan Hewani di Imari Japanese Restaurant JW Marriott Hotel Surabaya - Eka Rizqita Nur Syafiha Sari; Niken Purwidiani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to evaluate the implementation of SOPs for the preparation of animal ingredients, a critical point in food safety (potentially hazardous foods) at Imari Japanese Restaurant, JW Marriott Hotel Surabaya. Data were collected through kitchen observations, documentation studies, and interviews with Sous Chefs, Demi Chefs, and Commis, focusing on seven stages of ingredient preparation. The results showed that SOP implementation varied due to the phenomenon of "operational compromise." Under normal conditions, the stages of thawing, trimming, cutting (using digital scales), and storage in the operational chiller were carried out precisely according to five-star standards. However, during peak hours, the pressure of serving time (service time) triggered staff negligence. This resulted in neglect of tool sanitation (knives and cutting boards) and work area tidiness, which risked cross-contamination.